Does the Customer Matter Most? Exploring Strategic Frontline Employees' Influence of Customers, the Internal Business Team, and External Business Partners. (January 2016) - Plouffe, Christopher R.; Bolander, Willy; Cote, Joseph A.; Hochstein, Bryan
Marketing relationships have evolved from simple dyadic transactions between the firm and its customers into scenarios in which the firm's frontline employees are required to manage a portfolio of stakeholder relationships. The authors begin by characterizing the "strategic" frontline employee (SFLE) as a focal marketing employee who, in the execution of his or her work, must influence a variety of stakeholder target groups, including (1) customers, (2) the internal business team, and (3) external business partners. The authors leverage data from SFLEs at two firms to explore the similarities and differences in SFLE influence tactic effectiveness across the three stakeholder groups. They find that the effectiveness of influence tactics in driving performance differs across stakeholder target types and, somewhat surprisingly, that the SFLE's influence of both the internal business team and external business partners has a greater effect on his or her performance than does influence directed at customers. The authors close with a discussion of the implications for theory and practice.